Development and implementation of a protocol for the prevention of Clostridioides difficile infections aimed at the improvement of nursing skills - Knežević Darija; Jović Duška; Egeljić-Mihailović Nataša; Dobrovoljski Daniela (Sestrinska reč, 2023)
Introduction: Hospitalized patients have an increased risk of developing infections caused by Clostridioides difficile. Due to the changing epidemiology of C. difficile, it is necessary to educate nurses about the implementation of prevention measures, but also about the criteria for obtaining a quality sample of feces in order to establish an etiological diagnosis in a timely manner. The aim of the study was to assess gaps and flaws in C. difficile infection (CDI) prevention policies and practices, and to determine whether a nurses knowledge about early identification and isolation of CDI patients improved after education. Methods: The research was conducted in a quasi-experimental study at the University Clinical Center of the Republka Srpska (UKC RS) in the period from May 2020 to December 2021 on a sample of 60 nurses. A survey questionnaire Centers for Disease Control and Prevention (CDC) was used as a research instrument and it was intended for the assessment of knowledge, attitudes and understanding about procedures for the prevention of infection with C. difficile. The applied strategy to prevent hospital CDI was based on the introduction of the concept of "package of care", which was based on scientific evidence. For the education of nurses, interactive educational modules were used that contained detailed prevention measures CDI in hospital conditions in accordance with the guidelines. Before and after the education, the participants completed a knowledge test about C. difficile and prevention CDI.The study was approved by the Ethics Committee of the UKC RS. Results: Only 5 (8.3%) respondents stated that they were informed about CDI prevention during the visit of a nurse from the infection control team. Most of the shortcomings during the assessment of CDI prevention at the observed clinics were related to the practice of sending feces samples for laboratory testing for C. difficile. Nurses showed highly statistically significant (p<0.001) better knowledge about the importance of early identification of C. difficile and isolation of CDI patients in the post-education test. Conclusions: The implementation of a CDI prevention protocol intended for nurses can be one of the algorithms that will precisely identify C. difficile, and thus successfully implement CDI prevention measures.